Kazakh Patriotic Consciousness: Political Science Aspects - Mukhanova, Gulmira B.; Absattarov, Galymzhan R. (International Journal of Criminology and Sociology, 2022)
The relevance of the subject matter is conditioned by the fact that the paper investigates the issues of Kazakhstani patriotic consciousness, which have not yet been studied in socio-political science. The paper is aimed at a detailed study of the nature and structure of the patriotic consciousness of the Kazakh population as a new type of patriotic consciousness. The leading methods to study this problem are modelling and analysis, which allow to comprehensively study and describe the components of the Kazakhstani patriotic consciousness as an object of study. Based on the research, it was concluded that the Kazakhstani patriotic consciousness is a complex managed system of ideas and views, traditions, and principles of behaviour, feelings and moods of the multinational multiconfessional people of Kazakhstan. The Kazakhstan patriotic consciousness is the result of the reflection in the consciousness of the population of a new type of Kazakhstan’s national homeland, which is aimed at uniting and rallying all the peoples of Kazakhstan, the progress of a democratic society in Kazakhstan. At the same time, the paper focuses on discussion issues that relate to the problems of optimising the formation and education of the patriotic consciousness of the population of Kazakhstan, including the problems of constructing their theoretical framework – the theory of Kazakhstani patriotic consciousness. The practical significance of the results is reflected in the fact that this study can serve as the basis for further in-depth study of the dynamics of the Kazakhstani patriotic consciousness and national policy of the Republic of Kazakhstan.